Detection of anti-enterovirus IgG in human sera by ELISA method using the KTL-510 peptide - Pellerova, Michaela; Albertova, Katarina; Simkova, Vanesa; Borsanyiova, Maria; Benkoova, Brigita; Kissova, Renata; Pastuchova, Katarina; Tauriainen, Sisko; Galama, Jochem M. D.; Bopegamage, Shubhada (FRONTIERS MEDIA SA, 2025)
Enterovirus (EV) infections occur frequently in humans. In some geographical areas they are more common. These viruses cause diseases with varying degrees of severity, from a simple respiratory tract infection to severe diseases. Since EVs include more than 70 serotypes currently circulating in the population, a methodology that detects most of them is needed. ELISA is a rapid, sensitive, and economical diagnostic method for the identification of EV serotypes and can also be used as a retrospective diagnostic tool or in the investigation of outbreaks of infection. Commercial EV-ELISAs often appear and gradually disappear from the market supply. We have used the KTL-510 peptide, a synthetic viral protein of poliovirus VP1, as an antigen in a peptide-based ELISA for the detection of a broader spectrum of anti-EV antibodies. We aimed to design, optimize, and standardize this in-house ELISA with the peptide, and implement the method for routine detection of anti-EV IgG in human sera. For determining the cut-off value, we used 100 patients' sera which were previously tested negative for IgG antibodies against EVs using a commercial ELISA kit available. We monitored patients' sera samples sent for serological testing of anti-coxsackievirus antibodies to the National Reference Center for the Identification of Enteric Viruses between 2018-2022. These serum samples were examined using a standard virus neutralization test as well as the newly developed ELISA method.